2014
DOI: 10.1159/000365863
|View full text |Cite
|
Sign up to set email alerts
|

Green Nail Syndrome (Pseudomonas aeruginosa Nail Infection): Two Cases Successfully Treated with Topical Nadifloxacin, an Acne Medication

Abstract: Green nail syndrome (GNS) caused by Pseudomonas aeruginosa is the most common bacterial nail infection. The treatment of GNS is challenging in many cases and recommendations based on clinical trials are lacking. We report two cases with GNS successfully treated with off-label use of topical nadifloxacin, a fluoroquinolone approved for acne and bacterial skin infections in some countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
2
7
0
3
Order By: Relevance
“…First of all, our study confirmed the previous findings that GNS tends to occur on a single digit, on the big toe or thumb, and with a significant association with onychomycosis 2,7 . While multiple GNS cases have been reported to be associated with Candida infection, 8–10 the specific number of these cases could not be identified in the present study due to insufficient description of the mycological examinations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…First of all, our study confirmed the previous findings that GNS tends to occur on a single digit, on the big toe or thumb, and with a significant association with onychomycosis 2,7 . While multiple GNS cases have been reported to be associated with Candida infection, 8–10 the specific number of these cases could not be identified in the present study due to insufficient description of the mycological examinations.…”
Section: Discussionsupporting
confidence: 87%
“…First of all, our study confirmed the previous findings that GNS tends to occur on a single digit, on the big toe or thumb, and with a significant association with onychomycosis 2,7 . While multiple GNS cases have been reported to be associated with Candida infection, 8–10 the specific number of these cases could not be identified in the present study due to insufficient description of the mycological examinations. Our data also revealed that there is no sex difference among the affected patients and that fluoroquinolones have good therapeutic efficacy, with 22 (64.7%) patients showing complete clearance and eight (23.5%) showing notable improvement before they were lost to the follow up; it should be noted, however, that onychomycosis can be a predisposing factor of GNS as P. aeruginosa is an opportunistic pathogen.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Table 1 lists the drugs used to treat acne by topical application of nanoparticle systems. These new formulations have been shown to provide efficacy, tolerability, compliance, and cosmetic acceptability [72,73]. …”
Section: Topical Applications Of Nanoparticlesmentioning
confidence: 99%
“…He was started on topical polymyxin B cream for 2 months with a view to extend treatment depending on progress. Other treatment options for Pseudomonas nail infections such as topical nadifloxacin18 and tobramycin drops19 have been reported, but they were not available in Canada.…”
Section: Treatmentmentioning
confidence: 99%